Barriers to Worldwide Access for Paxlovid, a New Treatment for COVID-19. (7th April 2022) - Pepperrell, Toby; Ellis, Leah; Wang, Junzheng; Hill, Andrew
Abstract: Pfizer and the Medicines Patent Pool (MPP) have reached a voluntary licensing agreement for Paxlovid (nirmatrelvir+ritonavir), a novel antiviral for coronavirus disease 2019 (COVID-19) taken orally in the first 5 days from symptom onset. The Pfizer-MPP deal enables 95 low- and middle-income countries (L/MICs) to access affordable biosimilars. Generics are delayed awaiting bioequivalence testing and may be ineffective in L/MICs with reduced testing capacity, which comprise only 10% of global diagnoses. Thirty-nine percent of diagnoses originate in MICs forced to pay high prices due to exclusion from the Pfizer-MPP deal. The cost-effectiveness of Paxlovid could be limited compared with the creation of sustainable vaccine infrastructure in these nations, delaying socioeconomic pandemic recovery. Furthermore, Paxlovid may not be cost-effective in vaccinated populations, and concerns remain over ritonavir drug interactions with COVID-19 comorbidity medications. We call for expanded coverage by the Paxlovid-MPP deal and greater access to testing.